Transactions on environment and electrical engineering (EEEIC International Publishing, 2015)
Interdisciplinary journal that publishes original research articles, review articles, and case studies in all areas of Electrical, Electronic and Environmental Engineering.
Keywords: Electrical engineering : Environmental aspects : Periodicals; Electric power-plants : Environmental aspects : Periodicals; Renewable energy sources : Periodicals; Electrical engineering : Periodicals; Environmental engineering : Periodicals; Electric power-plants : Environmental aspects; Electrical engineering; Environmental engineering; Renewable energy sources; Electrical Engineering